Community Participation in Project Planning: A panacea to improved Performance of Community Water Supply Projects in Kericho County, Kenya - Korir, Justus K.; Kyalo, Dorothy N.; Mbugua, John (Advances in Social Sciences Research Journal, 2021)
This article sought to investigate the influence of community participation in project planning on the performance of community water supply projects in Kericho County, Kenya. The indicators used to assess this included community participation in; Scope planning, Activity planning and Resource planning. The study adopted descriptive survey design and correlation research design. The descriptive survey design was used to describe characteristics of the population being studied whilst a correlational research was used to describe the degree to which variables under the study were related. The target population comprised 8369 people from which a sample of 382 was considered and out of which 310 responded. The sample comprised of household heads, management committee members and sub-County water officers. The research instruments for this study were: questionnaires, focus group discussion and interview schedules. Stratified proportional sampling, random sampling and census techniques were used to collect primary qualitative and quantitative data. The data was compiled, given codes and input into SPSS version 25 computer program for statistical analysis and presentation. The study findings showed that community participation in scope planning (R=0.580, p=0.00<0.05, R2=0.334), activity planning (R=0.538, p=0.00<0.05, R2=0.288) and resource planning (R=0.511, p=0.00<0.05, R2=0.259) are significant explanatory variables with respect to project performance at 95% confidence level. Therefore, the study concluded that the community should be encouraged to actively participate more during the planning process in order to enhance the performance of their community water supply projects. In this regard, the study recommends that policies to facilitate the structured participation of the community could be enacted to guarantee participation and hence improve the performance of community water supply project.